The Effect of Brand Image and Nutrition Label on The Purchase Intention of Lawson's Ready-To-Eat Minimarket Products Mediated By Price - Arlansah, Ripki; Gularso, Kurnadi (Pelopor Publikasi Akademika, 2024)
This study examines the influence of brand image and nutrition label on purchase intention for ready-to-eat products with price as a mediating factor. The data was collected through a non-probability sampling method using a google form online questionnaire, with a total 164 respondent who had purchased ready-to-eat Minimarket Lawson products. This study utilized Partial Least Square SEM. brand image and nutrition label variables as dependent variables, purchase intention as independent variables, and price as a mediating variable. The results of this study indicate that brand image has a positive and significant effect on price, nutrition label has a positive and significant effect on price, brand image has a positive and significant effect on purchase intention, nutrition label has a positive and significant effect on purchase intention, price has a positive and significant effect mediating brand image on purchase intention, price has a positive and significant effect mediating nutrition label on purchase intention.